Factores socioeconómicos y culturales que influyen en la demanda de una carrera universitaria en la libertad: una aplicación del análisis cluster - Moreno Rodríguez, Rosa Ysabel (2012)
In the present research, the demand that university careers experience from fifty-year students of public and private high schools in the Department of La Libertad, Peru has been analyzed having into account the influence of socio-economic and cultural factors in their final decision to choose a career. The data collection was carried out by means of focus group techniques, interviews in depth, a survey to measure the socio-economic level, a personality test and a questionnaire with social and cultural variables. The probabilistic sample was made up of twenty eight students from thirteen different provinces of the Department of La Libertad. A multi-factorial design was considered due to the interaction of the investigated variables. The information was processed using cluster analysis and group analysis (Hair, 1999) which try to relate variables so that the individuals’ responses can be grouped together in relation to their similarities. Values, aptitudes, personality, family search of social prestige and socio-economic level all influence in determining the demand for a university career by fifth – year high school students. According to their profiles, the students can be organized as follows: a) Enterprising: They are responsible and they have a passionate personality. They opt for Accounting and Administration. Their parents do not influence on their career election and they aspire to having prestige and social status. b) Progressive: They are respectful and honest. They like their parents’ profession. They are sentimental or nervous and opt for Engineering, Law or Medicine. They seek personal prestige. c) Ambitious: They are solidarious and they have a phlegmatic personality. They are calm or apathetic and opt for Education or Biological Sciences. They admire their neighbors’ profession and do not know their community. They aspire to getting some status in their community.